Realization of image cryptography using FPAA-based two chaotic systems - Sanprang, Pitipat; Amornsusawad, Chinnapat; Boonmak, Kuntapong; Chimnoy, Jirat; Karawanich, Khunanon; Prommee, Pipat (My University, 2023)
This paper presents a data cryptography system based on chaotic systems (Lorenz and jerk). The system implementation consists of Field Programmable Analog Array (FPAA) and a microcontroller for transmit and receiver sides. MATLAB/Simulink provides the simulation results in various parameters. The experimental setup is exhibited by applying the data of digital pictures, which are encrypted by the selected chaos model and transmitted by using the serial port. The receiver can be correctly decrypted if and only if the chosen chaos model and parameters are perfectly matched with the transmitter. The experimental results of BER were measured around $42.39\times 10^{-6}$ for the Lorenz system and $38.29\times 10^{-6}$ for the jerk system with a time of approximately 24 minutes to recover all 10,002,432 bits
Keywords: Chaotic System; Cryptography; FPAA; Image encryption